Rancang Bangun dan Implementasi Energy Monitoring System di Sekolah Darul Hikam - Ayu Laksmi Padmadewi; Mugni Labib Edypoerwa; Umar Hanif Ramadhani; Yadi Mulyadi; Bambang Trisno (Universitas Widyatama, 2026)
The use of electrical energy in educational institutions continues to increase in line with the growing need for facilities and infrastructure. However, the absence of a proper monitoring system makes it difficult to evaluate energy consumption in real time. This study designs and implements an Energy Monitoring System (EMS) based on the PZEM-004T sensor at Darul Hikam School. The system records electrical parameters including voltage, current, power, energy, frequency, and power factor. All data are stored on an online server and can be accessed in real time through a web-based dashboard. Test results show that the system is capable of recording an average voltage of 218–228 V, current in the range of 0–20 A, and a peak load of up to 4300 W. With the implementation of EMS, the school is able to identify energy consumption patterns, detect inefficient loads, and develop effective saving strategies. The system has proven to be reliable as an energy monitoring solution in educational environments.